Welcome to Dunder Mifflin: the ultimate oral history of The office (Custom House, an imprint of HarperCollins Publishers, 2021)
"The official oral history book of The Office, featuring exclusive interviews with every major player and never-before-seen photos, pulling back the curtain on the absurdity and genius that went in to creating this unstoppable force in American popular culture and why it continues to resonate with audiences today." -- Provided by publisher.
Preface. How did we get here? / by Brian Baumgartner , "Okay, here's the pitch": the Office travels across the Atlantic , "Scranton hot": casting the lovable misfits of Dunder Mifflin , "Everything that makes it harder makes it better": making the pilot , "Let me tell you why this isn't going to work": making season one , "The office needed a billion things to go right": the emotional roller coaster of season two , "John and I are not a couple": the office love stories , "Inheritors of the history of comedy": the comedy tropes that inspired and shaped the Office: season three , "I don't care, fire me!": Inside the Office writers' room...and the writers strike that nearly ended the show: season four , "The moment that my life changed": a wedding, new hires (and losses), and other shake-ups: seasons five and six , "Losing the captain of our ship": the long goodbye for Michael Scott (and Steve Carell): season seven , "Who should be the boss?": The search for a new Dunder Mifflin regional manager: seasons eight and nine , "It's a wrap": the series finale , "Beauty in ordinary things": the legacy of the Office.